The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2012
DOI: 10.1038/bjc.2012.239
|View full text |Cite
|
Sign up to set email alerts
|

mRNA profiling of the cancer degradome in oesophago–gastric adenocarcinoma

Abstract: Background:Degradation of the extracellular matrix is fundamental to tumour development, invasion and metastasis. Several protease families have been implicated in the development of a broad range of tumour types, including oesophago–gastric (OG) adenocarcinoma. The aim of this study was to analyse the expression levels of all core members of the cancer degradome in OG adenocarcinoma and to investigate the relationship between expression levels and tumour/patient variables associated with poor prognosis.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
25
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 58 publications
(102 reference statements)
5
25
0
Order By: Relevance
“…12,26 Furthermore, no correlation was found with TNM stage, although a previous study has revealed differing results. 25 Survival analysis demonstrated that patients with positive ADAM8 expression have shorter survival times than those with negative expression and that this protein is an independent predictor of poor survival of GC patients, which is consistent with the results of studies on lung, renal, and brain cancers. [27][28][29] Although ADAM8 is involved in several types of cancers, few data have been obtained with regard to its mechanism of action.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…12,26 Furthermore, no correlation was found with TNM stage, although a previous study has revealed differing results. 25 Survival analysis demonstrated that patients with positive ADAM8 expression have shorter survival times than those with negative expression and that this protein is an independent predictor of poor survival of GC patients, which is consistent with the results of studies on lung, renal, and brain cancers. [27][28][29] Although ADAM8 is involved in several types of cancers, few data have been obtained with regard to its mechanism of action.…”
Section: Discussionsupporting
confidence: 81%
“…Although ADAM8 is upregulated in various types of human solid tumors, 25,26 this is the first study to explore its precise effect on gastric carcinogenesis. Both the significant increase in the ADAM8 mRNA level and the greatly increased percentage of ADAM8 protein expression in GC tissues observed in this study indicate that this protein is involved in the initiation and progression of GC.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we have demonstrated that ADAM12-mediated HB-EGF shedding plays a critical role in gastric cancer development in a preclinical model (34). Although there have been two studies of the presence of ADAM12 in gastric cancer (35) and esophagogastric junctional adenocarcinoma tissues (36) in which protein or mRNA of ADAM12 was highly expressed, there have been no reports to date of the presence of ADAM12 in the urine or serum of patients with gastric cancer. MMPs, which can be produced by both tumor and stromal cells, are a multigene family of metal-dependent degradative enzymes that are required for extracelluar matrix remodeling Immunohistochemical analyses of MMP-9, NGAL, and ADAM12.…”
Section: Discussionmentioning
confidence: 94%
“…The expression levels of several MMPs and other metzincin family proteinases have been previously reported to be significantly increased and directly correlate with the invasiveness of many tumors including lung, prostate, stomach, colon, breast, ovary and oral squamous cell cancers. 52–57 Generally, the expression of high levels of multiple MMP family members correlates positively with tumor aggressiveness, including increased invasive capacity, metastasis and poor patient survival. 24 Although we have observed similar trend in the overexpressions of MMPs in our study, only MMP1 is significantly expressed in aggressive tumors compared with non-aggressive tumors.…”
Section: Discussionmentioning
confidence: 99%